Globalizing whiteness? Visually re/presenting students in global university rankings websites. Issue 6 (2nd November 2019) - Estera, Annabelle; Shahjahan, Riyad A.
ABSTRACT: Amid debates about the role and impact of global university rankings (GURs), very few have closely examined how GURs media outlets construct meanings of higher education (HE) in their visual representations. We critically examine publicly available visual media of students in the Times Higher Education World University Rankings and US News and World Report websites. Drawing on Stuart Hall's heuristics of representation and attending to visual grammars, we argue whiteness maintains its racial hegemony in GURs' student imagery through its flexibility and in/visbility. Furthermore, whiteness is entangled with other systems of oppression, particularly patriarchy, homonormativity, and heterosexuality. We suggest that GURs rankings media are not simply constructing and informing us about the quality and excellence of HE, but simultaneously teaching us how to view students, often reproducing oppressive racialized and gendered ideologies. We end with methodological implications of visual cultural studies in comparative education.